Synaptic remodeling of neuronal circuits in early retinal degeneration - Soto, Florentina; Kerschensteiner, Daniel (Frontiers in Cellular Neuroscience, 2015)
Photoreceptor degenerations are a major cause of blindness and among the most common forms of neurodegeneration in humans. Studies of mouse models revealed that synaptic dysfunction often precedes photoreceptor degeneration, and that abnormal synaptic input from photoreceptors to bipolar cells causes circuits in the inner retina to become hyperactive. Here, we provide a brief overview of frequently used mouse models of photoreceptor degenerations. We then discuss insights into circuit remodeling triggered by early synaptic dysfunction in the outer and hyperactivity in the inner retina. We discuss these insights in the context of other experimental manipulations of synaptic function and activity. Knowledge of the plasticity and early remodeling of retinal circuits will be critical for the design of successful vision rescue strategies.